2009
DOI: 10.1038/nchem.440
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative molecular dynamics in surface reactions

Abstract: The controlled imprinting of surfaces with specified patterns is important in the development of nanoscale devices. Previously, such patterns were created using self-assembled physisorbed adsorbate molecules that can be stabilized on the surface by subsequent chemical bonding. Here we show a first step towards use of the bonding within a surface to propagate reactions for patterning, namely the cooperative reaction of adjacent silicon atoms. We exploit the double-bonded silicon dimer pairs present on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
70
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 34 publications
1
70
0
Order By: Relevance
“…Surface buckling similar to the features marked "b" in Fig 1 was previously observed for 1,5-dichloropentane and also for pairs of 1-fluoropentane molecules (13,14). Exhaustive calculations showed that the buckling arose because of the asymmetry of these molecular pairs, which caused a buildup of charge and hence brightness at a silicon dimer located to one side of the adsorption site (13,14).…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…Surface buckling similar to the features marked "b" in Fig 1 was previously observed for 1,5-dichloropentane and also for pairs of 1-fluoropentane molecules (13,14). Exhaustive calculations showed that the buckling arose because of the asymmetry of these molecular pairs, which caused a buildup of charge and hence brightness at a silicon dimer located to one side of the adsorption site (13,14).…”
Section: Resultsmentioning
confidence: 61%
“…Linear self-assembly was found to be due to dipole-directed assembly (DDA) in which the displacement of surface charge, caused by an initial physisorption event, rendered an adjacent surface site attractive to subsequent physisorption (13). A further finding pertinent to the present study was the identification of "cooperative" surface reaction in which the first molecule of a physisorbed pair of halides (fluoropentane molecules) invariably triggered the reaction of the second molecule of the pair (14). Cooperative reaction was shown to occur for reactions initiated by heat or electrons.…”
mentioning
confidence: 68%
See 3 more Smart Citations